Rulebook vs. Reality : The Influence of University AI Policies on Student AI Aversion, Attitudes, and Expected Learning Outcomes - Fidder, Daan (My University, 2024)
This study investigates students’ general attitudes toward AI and the impact of university AI policies on their attitudes, algorithm aversion, and expected learning outcomes. Utilizing a mixed-methods approach, we conducted document analyses of AI policies from Dutch universities and a scenario-based survey experiment with students. The results of our exploratory analysis revealed that students are highly familiar with AI tools and generally hold positive views regarding the future of AI, although concerns about potential biases persist. The findings from our empirical research indicate that while policies do not directly influence students’ trust in AI, restrictive policies prohibiting AI usage lead to a slight change in attitudes. Notably, policies significantly influence the use of AI, with students utilizing AI most frequently in the absence of specific policies. These findings underscore the importance of well-crafted AI policies that promote transparency, fairness, and ethical use to maximize educational benefits. Future research should explore diverse factors and conduct longitudinal studies to further elucidate the long-term effects of AI policy integration. This study contributes to the ongoing discourse on AI in education by highlighting the critical role of policy in shaping students’ engagement and learning outcomes with AI technologies.